Peat water treatment by adsorption using kaolin-based geopolymer. Issue 1 (May 2020) - Utama, PS; Olivia, M; Prawiranegara, BA; Agusti, ID; Pinem, JA; Darmayanti, L; Saputra, E
Abstract: Geopolymers have zeolite-like chemical compositions, which has some characteristics such as wide surface area and excellent stability so that it can be used for adsorbents for peat water treatment. In this research, the kaolin based geopolymers were applied as an adsorbent for processing the peat water into clean water. The variable used in this research were adsorbent mass (1; 1.5; 2; and 2.5 g), and time (30; 60 and 90 minutes). The results indicated that the kaolin-based geopolymers were very efficient in removing color and organic content. The optimum condition was mass adsorbent of 1 g and time of 30 min, and the result was 100% for removing color and 98.77% for removing organic content.